Nonvoters America's no-shows - Doppelt, Jack C.; Shearer, Ellen, 1952-; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
'Nonvoters' addresses the issue of why 51.2 percent of the population of the USA failed to vote in the November 1996 presidential election.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States. -- Congress -- Elections, 1996.; Voting -- United States -- Case studies; Political participation -- United States -- Case studies; Electronic books